Unveiling Spousal Challenges and Expectations in Caring for Elderly Dementia Patients in Indonesia - Pradana, Anung Ahadi; Rohayati, Rohayati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: Dementia is a progressive, terminal condition causing cognitive decline and dependency on caregivers, often spouses. Spousal caregivers face unique challenges, including physical, emotional, social, and financial burdens. However, limited research in Indonesia has explored the lived experiences, challenges, and expectations of spousal caregivers for elderly dementia patients. Objective: This study aims to uncover the challenges and expectations of spousal caregivers for elderly dementia patients in Bekasi, Indonesia, to inform tailored support interventions. Methods: Using a qualitative descriptive phenomenology approach, in-depth semi-structured interviews were conducted with 10 spousal caregivers. Participants were selected purposively, meeting inclusion criteria such as caregiving duration of over six months. Data were analyzed systematically through thematic analysis, validated via peer review and participant feedback. Results: Two main themes emerged: (1) Optimal conditions expected of a partner, including hopes for condition improvement and miraculous recovery; and (2) Improving self and family conditions, involving desires to maintain caregiving responsibilities, avoid burdening children, and foster harmonious household relationships. Participants emphasized the importance of societal and governmental support for dementia care. Conclusion: Spousal caregivers in Indonesia face significant challenges yet maintain optimistic expectations for their partners and families. This highlights the need for community-based monitoring systems and tailored interventions to reduce caregiver burden and improve dementia care quality.